Kinetic Continuous Opinion Dynamics Model on Two Types of Archimedean Lattices - Lima, Francisco W. S. (Frontiers in Physics, 2017)
Here, the critical properties of kinetic continuous opinion dynamics model are studied on (4,6,12) and (4,8^2) Archimedean lattices. We obtain p_c and the critical exponents from Monte Carlo simulations and finite size scaling. We found out the values of the critical points and Binder cumulant that are p_c=0.086(3) and O_4^*=0.59(2) for (4,6,12); and p_c=0.109(3) and O_4^*=0.606(5) for (4,8^2) lattices and also the exponent ratios β/ν, γ/ν and 1/ν are respectively: 0.23(7), 1.43(5) and 0.60(3) for (4,6,12); and 0.149(4), 1.56(4) and 0.94(4) for (4,8^2) lattices.